Prototype Development and Demonstration of Hierarchical Software-Defined Optical Network - Ruiquan Jing; Chengliang Zhang (Dianxin kexue)
For OTN，a control mechanism for multi-domain optical networks with commercial OTN equipments by using hierarchical SDN controller was demonstrated.This experiment is the first demonstration of hierarchical control over multiple domain OTN equipments with extended OpenFlow protocol.This capability will be valuable for carriers providing end-to-end services in multi-vendor environment at the lowest cost with expected scale and performance.